THE EFFECT OF PARENTS OF PARENTS OF THE PARENTS AND THE POSITION OF CHILDREN WITH FAMILY STRENGTHS ON SELF-ASSISTANCE OF TK CHILDREN IN THE GROUP OF BANGKARI KELOMPOK B PALANGKARAYA - Charmila. R, Seli; Wahdini, Erny; Suriansyah, Ahmad (Journal of K6, Education and Management, 2019)
The purpose of the study was to determine the effect of parenting and child position on family attachment to the independence of children in the Palangka Raya sun group TK B group Jekan Raya sub-district, Palangkaraya city. The approach of this research uses quantitative with expalatory method, namely causation. The population of this study amounted to 118 with proportional sampling techniques with a sample of 92 people. The research instrument used a questionnaire, data analysis using regression analysis and path analysis. The results showed that path analysis showed that the results of the level of contribution from the path analysis from the direct relationship of parenting through family attachment to independence was found to be the level of the indirect relationship is 0.247 x 0.928 = 0.229, the indirect relationship is a positive indirect relationship of parenting old through family attachment to independence is 0.229. This means that there is an indirect relationship between parenting through family attachment to independence in the Palangka Raya sun group TK B group, Jekan Raya sub-district, Palangkaraya city. The results of r square analysis show that 0.875 = 87.5% gives the effect of family attachment to children's independence. The results of the path analysis from the direct relationship of parenting through family attachment to independence with Standardized Coefficients beta amounted to 0.304 and 0.929, it can be seen the level of indirect relationship is 0.304 x 0.929 = 0.229 then the indirect relationship is a positive indirect relationship pattern Parental care through family attachment to independence is 0.229. The results of r square analysis show that 0.886 = 88.6% gives the influence of the position of the child through family attachment to the independence of the child.